2016
DOI: 10.1002/tre.501
|View full text |Cite
|
Sign up to set email alerts
|

Reactive arthritis: can't see, can't pee, can't climb a tree…

Abstract: Reiter's disease, also known as reactive arthritis, is a seronegative HLA‐B27‐associated autoimmune disease, characterised by oligoarthritis of large joints with additional ophthalmic and urological manifestations. Many will recall the aide‐mémoire ‘can't see, can't pee, can't climb a tree’ from their medical school days. This article describes the history and aetiology of Reiter's disease, along with its treatment and prognosis, and reminds readers to be vigilant for its characteristic signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Conjunctivitis is one of the most common ocular manifestations of reactive arthritis; other associated ocular entities include uveitis, episcleritis, scleritis, and keratitis. [149] Conjunctivitis in reactive arthritis entities manifests itself as conjunctival hyperemia with purulent discharge. Occurring in nearly one third of the patients, conjunctivitis is an essential component of the "Reiter's triad".…”
Section: Reactive Arthritismentioning
confidence: 99%
“…Conjunctivitis is one of the most common ocular manifestations of reactive arthritis; other associated ocular entities include uveitis, episcleritis, scleritis, and keratitis. [149] Conjunctivitis in reactive arthritis entities manifests itself as conjunctival hyperemia with purulent discharge. Occurring in nearly one third of the patients, conjunctivitis is an essential component of the "Reiter's triad".…”
Section: Reactive Arthritismentioning
confidence: 99%
“…However, when it comes to genitourinary infections, the risk is higher for men than women with 9:1 ratio [1]. Another study has shown that females are more exposed than male [10].…”
Section: Is the Epidemiology Of Rea Changing?mentioning
confidence: 99%